Characteristics and Epidemiology of Discharged Pneumonia Patients in South Korea Using the Korean National Hospital Discharge In-Depth Injury Survey Data from 2006 to 2017 - Kyunghee Lee; Kyunglan Hong; Sunghong Kang; Jieun Hwang (MDPI AG, 2021)
Despite the use of vaccines and various antibiotics, approximately 30% of the South Korean population is treated for pneumonia each year, and the number of deaths from pneumonia continues to increase. The present study used information on discharged patients in South Korea to investigate the number and characteristics of discharged pneumonia patients across 12 years. Using the Korean National Hospital Discharge In-Depth Injury Survey data, information on discharged patients from 2006 to 2017 were collected. The number of discharged pneumonia patients for each year and their age group was assessed, and the Charlson Comorbidity Index was used to assess the risk of comorbidities in these patients. The number of discharged pneumonia patients varied every year in South Korea. In particular, the total number of patients increased substantially in 2011, with a large increase in the number of infants and children. In addition, the number of discharged pneumonia patients increased in the elderly group compared to the other age groups. Moreover, a recent increase in the severity of comorbidities in pneumonia patients was noted. Given the continued increase in the number of elderly patients with pneumonia, chronic diseases, such as hypertension and diabetes, should be managed first in the elderly. Moreover, appropriate treatment methods should be selected based on the presence of comorbidities.